Long-Term Assessment of Soil Salinization Patterns in the Yellow River Delta Using Landsat Imagery from 2003 to 2021 - Yu Fu; Pengyu Wang; Wengeng Cao; Shiqian Fu; Juanjuan Zhang; Xiangzhi Li; Jiju Guo; Zhiquan Huang; Xidong Chen (Land)
The Yellow River Delta (YRD), as a key area for the economic development of the Bohai Rim region, significantly impacts soil fertility and plant growth through soil salinization content. Accurately determining the spatial distribution of soil salinization in the YRD is vital for regional salinity management and agricultural development. In this study, we constructed and evaluated three soil salinization indices—NDSI, SI, and S5—using measured soil conductivity data and three machine learning methods: Random Forest, Support Vector Machine, and XGBoost. The results indicate that the Support Vector Machine achieved the best inversion effect on regional salinization levels, with an Area Under Curve (AUC) value of 0.88. The salinization level in the YRD has shown an increasing trend over the years, decreasing spatially from north to south, from east to west, and from the coast inland. From 2003 to 2009, salinization was primarily concentrated in northern and eastern coastal areas, while from 2009 to 2021, it gradually expanded inland. The salinized area increased from 538.4 km2 in 2003 to 761.5 km2 in 2021, particularly between 2009 and 2015, with a 47.95% increase. The main factors influencing salinization in the YRD were distance from the Bohai Sea, seasonal average potential evapotranspiration, and seasonal average normalized vegetation index, with interaction-driven effects being stronger than single-factor effects. This study provides crucial scientific support for sustainable salinization management and ecological restoration in the Bohai Sea region.